UMKM Empowerment Through E-Content Development and Strategic Marketing Communication Training in Economic Digitalization Efforts for UMKM Batik Tamanan Bondowoso Regency - Setyo Wibowo, Nugroho; Sugiartono, Endro; Widianta, Moh. Muniha Dian; Atmadji, Ery Setiyawan Jullev (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Micro, Small and Medium Enterprises (UMKM) in Bondowoso Regency have an important role in economic growth and regional business development. To empower and improve the quality of UMKM in Bondowoso Regency, an UMKM empowerment program is carried out through E-Content Development and Strategic Marketing Communication skills training which can help Ijen Batik Tamanan UMKM in Bondowoso Regency in overcoming the challenges of digitalization and improving and expanding marketing. Economic digitalization plays an important role in accelerating the growth of Batik UMKM. Through the application of digital technology, UMKM can increase the visibility of their products online, reach a wider market, and strengthen interactions with customers through digital platforms and social media. Digitalization also opens up new opportunities to improve operational efficiency and management of UMKM businesses. UMKM can also understand how to develop effective and targeted marketing strategies to reach a wider range of consumers.